2004
DOI: 10.1128/jb.186.8.2303-2308.2004
|View full text |Cite
|
Sign up to set email alerts
|

The Tp38 (TpMglB-2) Lipoprotein Binds Glucose in a Manner Consistent with Receptor Function in Treponema pallidum

Abstract: A 38-kDa lipoprotein of Treponema pallidum (Tp38) was predicted to be a periplasmic sugar-binding protein based on its sequence similarity to the glucose/galactose-binding ( Treponema pallidum, the spirochetal agent of syphilis, continues to be highly enigmatic. Despite the availability of T. pallidum genome sequence information (11), many fundamental aspects of the organism's basic physiology and metabolism remain obscure (30). In this regard, members of our laboratory previously reported that a 38-kDa membra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
23
1

Year Published

2004
2004
2019
2019

Publication Types

Select...
9
1

Relationship

6
4

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 43 publications
1
23
1
Order By: Relevance
“…In classical gramnegative organisms, the ABC transporter MglABC has specificity for galactose (126,212). The homologous Mgl system in T. pallidum (21,236,299) may also bind galactose, but it has been speculated that, because of its inability to utilize galactose as a carbon source, T. pallidum may utilize MglABC as a glucose transporter (81). Ribose may be taken into the cell via an ABC transporter with homology to the RbsAC transporter system in the related spirochete Borrelia burgdorferi; however, carbon utilization studies demonstrated that ribose is not degraded by T. pallidum (217).…”
Section: Limited Metabolic Capacitymentioning
confidence: 99%
“…In classical gramnegative organisms, the ABC transporter MglABC has specificity for galactose (126,212). The homologous Mgl system in T. pallidum (21,236,299) may also bind galactose, but it has been speculated that, because of its inability to utilize galactose as a carbon source, T. pallidum may utilize MglABC as a glucose transporter (81). Ribose may be taken into the cell via an ABC transporter with homology to the RbsAC transporter system in the related spirochete Borrelia burgdorferi; however, carbon utilization studies demonstrated that ribose is not degraded by T. pallidum (217).…”
Section: Limited Metabolic Capacitymentioning
confidence: 99%
“…In fact, genome analysis predicts that T. pallidum devotes as much as 3% of its genetic coding capacity to lipoproteins (15). However, to date, with one exception (9,16), comparative sequence analyses have not been fruitful for predicting the functions of treponemal lipoproteins, and the inability to cultivate (and thus genetically manipulate) the organism has precluded using classical gene inactivation approaches (17) for investigating the functions of treponemal membrane lipoproteins.…”
mentioning
confidence: 99%
“…The mechanism(s) by which the parasite acquires and utilizes these essential nutrients can potentially help explain the peculiar membrane biology of T. pallidum, elucidate key aspects of its parasitic strategy, and prompt new avenues of investigation for potentially novel antimicrobial drug targets. To this end, we have found that many of the likely transport systems of T. pallidum are predicated on the organism's membrane lipoproteins (5)(6)(7)(8)(9)(10)(11)(12)(13), and, as a result, the organism devotes a large percentage of its genome to encoding these lipoproteins (3,14,15). Unfortunately, many of the putative lipoproteins are hypothetical (i.e.…”
mentioning
confidence: 99%